FROM DIGITAL ACCESS TO PERCEIVED ACADEMIC VALUE: A DOCUMENTARY CASE SYNTHESIS - Sherina Wulan Komalig; Johny Taroreh; Amsje Norma Winokan (EDUCATIONE, 2026)
Digital access does not automatically create academic value when evaluative skills, connectivity, assessment, and attention are uneven. This study examined how institutional policy, curriculum integration, student digital practices, and implementation constraints shaped the perceived learning value of digital literacy in Grade XI at SMA Negeri 1 Amurang, Indonesia. Because the available record did not include raw transcripts, participant counts, fieldwork dates, or numerical achievement data, the article is presented as a documentary qualitative case synthesis rather than a reanalysis of primary data. The synthesis draws on the study report's summaries of interviews with students, teachers, and school leaders, classroom and laboratory observations, curricula, lesson plans, academic records, and student digital products. Reported evidence indicates that ethical-use policies, teacher development, broad in-school access, and a recurring 30-minute literacy period supported implementation. Cross-subject content creation and use of Google services, AI tools, and Canva were perceived to strengthen conceptual clarification, collaboration, and assignment quality. These benefits were constrained by unequal home access, unstable networks, distraction, and inconsistent assessment criteria. No causal effect on grades was estimated. The study offers a provisional institutional-curricular implementation heuristic in which policy and infrastructure enable opportunities, curriculum and pedagogy convert them into purposeful practice, and assessment, ethics, self-regulation, family support, and access conditions shape perceived academic value. Future multi-site research should test these relationships with performance-based digital-literacy measures and longitudinal achievement indicators.